2020
DOI: 10.1093/rheumatology/kez682
|View full text |Cite
|
Sign up to set email alerts
|

Targeting bioenergetics prevents CD4 T cell–mediated activation of synovial fibroblasts in rheumatoid arthritis

Abstract: Objectives We investigated the reciprocal relationship linking fibroblast-like synoviocytes (FLS) and T lymphocytes in the inflamed RA synovium and subsequently targeted cellular metabolic pathways in FLS to identify key molecular players in joint inflammation. Methods RA FLS were cultured with CD4 T cells or T cell conditioned medium (CD4CM); proliferation, expression of adhesion molecules and intracellular cytokines were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 47 publications
4
36
1
Order By: Relevance
“…*p < 0.05, Wilcoxon signed-rank test. 3-BrPa, 3-bromopyruvate Th cells [26]. In contrast to these findings, we demonstrate here that the migratory capacities of OASF and RASF are significantly reduced under stimulation with ThCM and also under stimulation with inflammatory cytokines, especially when applied in combination.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…*p < 0.05, Wilcoxon signed-rank test. 3-BrPa, 3-bromopyruvate Th cells [26]. In contrast to these findings, we demonstrate here that the migratory capacities of OASF and RASF are significantly reduced under stimulation with ThCM and also under stimulation with inflammatory cytokines, especially when applied in combination.…”
Section: Discussioncontrasting
confidence: 96%
“…In a recent study, Petrasca and colleagues demonstrated that Th cells promoted the aggressive phenotype in RASF by boosting glycolysis-confirmed here with our data-and this effect could be reversed by 2-deoxy-D-glucose (2-DG) or by the AMP analogue 5-aminoimidazole-4-carboxamide ribonucleotide [26]. An abrogation of the aggressive phenotype of RASF by 2-DG, a non-metabolizable glucose analogue which blocks glycolysis downstream of HK2, has also been described by others [19], and 2-DG has been shown to be effective in reducing the severity of arthritis in a mouse model [55].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The inflamed synovial lesions exclusively contain memory and effector T cells and these cells are exposed to metabolic cues imposed by the tissue environment. Besides having to share energy resources, lesional T cells will receive metabolic signals from neighboring cell populations, which are highly metabolically active [18]. A dominant metabolite encountered in the inflamed joint is lactate [19,20], a breakdown product of glucose, produced by metabolically active stromal cells, endothelial cells and invading immune cells.…”
Section: Glucose Utilization In Ra and Sle T Cellsmentioning
confidence: 99%
“…Heterozygous deletion of GLUT3 correlates directly with expression levels of GLUT3 and influences glycolysis rates in the human immune system ( 46 ), but the frequency of the GLUT3 copy number variant is not different among RA, multiple sclerosis and heathy control, providing no evidence for RA protection in deletion of GLUT3 ( 46 ), the study of which demonstrated GLUT3 is not necessary for glucose transfer in patients with RA. However, another study showed the mutual activation between CD4 + T cells and FLS, which resulted in increased proliferation and expression of glucose transporters GLUT1 and GLUT3 in FLS ( 47 ). In rat Arthritis model, arthritic rats showed cachexia, reduced adipocyte size, and downregulated GLUT4 in adipocyte membranes ( 48 ).…”
Section: Glucose Metabolism As An Arthritogenic Risk Factormentioning
confidence: 99%